Prenatal Diagnosis of Alobar Holoprosencephaly, Cyclopia, Proboscis, and Isochromosome 18q in the Second Trimester - Meike Bangma; Simone Lunshof; Diane Van Opstal; Robert J. Galjaard; Dimitri N.M. Papatsonis (Thieme Medical Publishers, Inc., 2011)
We would like to present a rare case of alobar holoprosencephaly (HPE) in a fetus diagnosed by routine sonography in the second trimester. Structural sonography demonstrated multiple facial anomalies including absent nasal bone, flat facial profile, hypotelorism, fusion of the orbits and proboscis. After counseling, termination of pregnancy was performed by vaginally administered misoprostol. Karyotyping of amniotic fluid cells revealed an isochromosome 18q, resulting in a trisomy 18q and monosomy 18p. A stillborn female of 390 g with several congenital anomalies was born. Postmortem examination demonstrated several anomalies including the HPE, cyclopia, double fused eye, absence of the nose, and the presence of a proboscis. In the literature only a few cases have been published.